2021
DOI: 10.3389/fgene.2021.795546
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Competing Endogenous RNA Network Associated With the Pathogenesis of Graves’ Ophthalmopathy

Abstract: Background: Growing evidence has recently revealed the characteristics of long noncoding (lncRNA)/circular RNA (circRNA)-microRNA (miRNA)-mRNA networks in numerous human diseases. However, a scientific lncRNA/circRNA-miRNA-mRNA network related to Graves’ ophthalmopathy (GO) remains lacking.Materials and methods: The expression levels of RNAs in GO patients were measured through high-throughput sequencing technology, and the results were proven by quantitative real-time PCR (qPCR). We constructed a protein-prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…What is certain is that it is a self-reactive lymphocyte-induced autoimmune disease in which immune tolerance is lost, leading to an immune response to TSHR that initiates remodeling of the orbital tissue. Recently, many researchers have tried to further explore TAO pathogenesis by comparing differentially expressed RNAs and proteins between control groups and case groups( Yue et al, 2021 ). In our research, among 50 tRFs found to be dysregulated in the TAO group by RNA sequencing, 2 tRFs (tRF5-GluCTC and tRF5-GluTTC) were upregulated and one (tRF1-ArgTCG) downregulated.…”
Section: Discussionmentioning
confidence: 99%
“…What is certain is that it is a self-reactive lymphocyte-induced autoimmune disease in which immune tolerance is lost, leading to an immune response to TSHR that initiates remodeling of the orbital tissue. Recently, many researchers have tried to further explore TAO pathogenesis by comparing differentially expressed RNAs and proteins between control groups and case groups( Yue et al, 2021 ). In our research, among 50 tRFs found to be dysregulated in the TAO group by RNA sequencing, 2 tRFs (tRF5-GluCTC and tRF5-GluTTC) were upregulated and one (tRF1-ArgTCG) downregulated.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs are a type of long-stranded multifunctional RNAs with a length of more than 200 that have been reported to act at many different levels of gene expression, including epigenetic regulation, transcriptional regulation, post-transcriptional regulation, and miRNA regulation (87). Salmena et al suggested the competitive endogenous RNA hypothesis for lncRNA-miRNA interactions (88), which is characterized as mutual interference between coding and non-coding RNAs via miRNA response elements, resulting in an extensive regulatory network in the transcriptome (69).…”
Section: Lncrna and Gomentioning
confidence: 99%
“…The down-regulated of miR-146a levels promotes the development of inflammation, while the up-regulated of its levels allow the remission or termination of the inflammatory response. It has been proposed that miR-155 plays a crucial role in the development of Th17 cells during autoimmunity ( 69 ). Also, miR-155 has an essential role in fibrosis by mediating TGF-1β1 signaling to drive collagen synthesis ( 83 ).…”
Section: Non-coding Rnamentioning
confidence: 99%
See 2 more Smart Citations